Diagnosis of external causes of population declines of wild species needs to be both quick and reliable - Jeremy D. Wilson; Rhys E. Green (Ecological Solutions and Evidence, 2025)
Abstract As scientists involved in identifying and helping to implement actions to conserve declining populations of threatened species, we are concerned at the mismatch between the speed and extent of many currently observed declines and the fitness‐for‐purpose and scale of implementation of conservation programmes. Accurate and rapid diagnosis of the external causes of declines should be an important component of most species conservation programmes. We propose a stepwise framework to ensure that this can be done in a timely way. Central to our proposals is the recognition that seeking a perfect diagnosis can foreclose options for successful remedial action in a rapidly accelerating conservation crisis. We therefore outline approaches that may be used when detailed data are lacking or sparse. Solution. Expand the use of the diagnostic processes we describe to identify and test effective actions to halt and reverse species' population declines.